Ecodesign in the Footwear Industry: proposal for a transforming market - Plentz, Natália Debeluck; Tocchetto, Marta Lopes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This research addresses the issue of environmental problems caused by the leather and footwear industry and the necessity of modernization in the sector when facing new demands of impact control and transformations in the market itself. The current production system is in crisis, making a bigger concern with the environment necessary. Even more when considering some parts of Brazil, since the manufacturing of footwear is responsible for a large quantity of generated residue in them. There are possibilities for the sector, from new materials to alternative production processes, including recycling and reuse to diminish impacts. Also, environmental management can be seen as an important competitive differentiator to companies, which with the adoption of such principles decrease production costs as well as the risks of not complying with the environmental legislation. For this reason, it is believed that uniting environmental management and ecodesign, from product project to the introduction of reverse logistics practices, can be the answer the segment needs. The loss reduction can also help in the recuperation of Brazilian market, that has been suffering with the entry of Asian products.